Penanganan Pasca Bencana Siklon Tropis Seroja melalui Logistik Kemanusian dengan Kepner-Tregoe Situation Appraisal - Gita Kurnia; Ferani Eva Zulvia; Betanti Ridhosari (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
The Seroja Cyclone disaster that occurred from April to May 2021 in several areas in East Nusa Tenggara, Indonesia, caused casualties and damage to residents' houses. With so many residents affected, logistical assistance is urgently needed for victims who are still surviving. Community service team of Universitas Pertamina, namely “Universitas Pertamina Tanggap Bencana (UPTB)”, is one of the institutions that carries out the distribution of logistical assistance to victims of the Seroja Cyclone disaster. The suitability of the location and type of aid is an important thing to consider in planning the distribution of humanitarian logistical assistance. Therefore, the UPTB team used the Kepner-Tregoe Situation Appraisal method to determine priority locations for the distribution of aid by analyzing the level of urgency, the potential for problem growth, and the seriousness of the Impact experienced by residents in several candidate locations. Based on the results of the analysis, it was determined that two priority locations would receive assistance, namely sub-district of Namosain and Waipare, Watumilok Village. The suitable types of aids for the two locations are also identified, namely basic necessities (groceries), medicines and building materials. Through the evaluation of the questionnaire, the residents rated that they were very satisfied with the distribution of the logistical assistance they received.